Design of 4 liters equipment for extraction of rice dust oil using supercritical fluid co2 - Camilo Fernández Barriga (2019)
Rice dust is a material considered waste; however it contains 20.51% oil in that variety NIR 43. Oil extraction from rice dust by using supercritic fluids showed more advantages than traditional methods. Since it is a fluid solute dissolution is easier . By being a gas it allows an easy separation of matrix which results in a faster, more efficient and selective extraction of oil. To design this 4 liter equipment we tried in the lab rice dust at different pressures and temperatures in order to get better performance without altering essential characeristics.